Chemical ozone loss in the Arctic winter 1994/95 as determined by the Match technique - Rex, Markus; von der Gathen, Peter; Braathen, G. O.; Harris, N. R. P.; Reimer, E.; Beck, A.; Alfier, R.; Krüger-Carstensen, R.; Chipperfield, M.; De Backer, H.; Balis, D.; O`Connor, F.; et al. (1999)
The chemically induced ozone loss inside the Arctic vortex during the winter 1994/95 has beenquantified by coordinated launches of over 1000 ozonesondes from 35 stations within the Match94/95 campaign. Trajectory calculations, which allow diabatic heating or cooling, were used totrigger the balloon launches so that the ozone concentrations in a large number of air parcels areeach measured twice a few days apart. The difference in ozone concentration is calculated foreach pair and is interpreted as a change caused by chemistry. The data analysis has been carriedout far January to March between 370 K and 600 K potential temperature. Ozone loss along thesetrajectories occurred exclusively during sunlit periods, and the periods of ozone loss coincidedwith, but slightly lagged, periods where stratospheric temperatures were low enough for polarstratospheric clouds to exist. Two clearly separated periods of ozone loss show up. Ozone lossrates first peaked in late January with a maximum value of 53 ppbv per day (1.6 % per day) at475 K and faster losses higher up. Then, in mid-March ozone loss rates at 475 K reached 34 ppbvper day (1.3 % per day), faster losses were observed lower down and no ozone loss was foundabove 480 K during that period. The ozone loss in hypothetical air parcels with average diabaticdescent rates has been integrated to give an accumulated loss through the winter. The most severedepletion of 2.0 ppmv (60 %) took place in air that was at 515 K on 1 January and at 450 K on20 March. Vertical integration over the levels from 370 K to 600 K gives a column lass rate,which reached a maximum value of 2.7 Dobson Units per day in mid-March. The accumulatedcolumn loss between 1 January and 31 March was found to be 127 DU (similar to 36 %).